1997
DOI: 10.1080/0266736970130110
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Aggressive Playground Behaviour by Means of a School‐wide ‘Raffle’

Abstract: This research focuses on inappropriate aggressive behaviour of children aged 5 to 7 years in the school playground. Lunchtime supervisors were trained to distribute raffle tickets as reinforcement for appropriate playground behaviour. The prize draw for the raffle was held at the end of the five week intervention period. Using an AB design, observing target behaviours pre and post-intervention, it was found that the number of kicks was reduced by 75 per cent and the number of hits by 47 per cent. The importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Disciplining an aggressor may therefore be more effective if one also reduces or removes any reinforcement the aggressor receives from peers. One way of achieving this might be to make it clear to all children that supporting aggressive behaviour is as unacceptable as aggression itself and by rewarding peers who behave appropriately [see Roderick et al, 1997, for an example of rewarding appropriate playground behaviour]. However, further research would be needed to test the efficacy of such a strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Disciplining an aggressor may therefore be more effective if one also reduces or removes any reinforcement the aggressor receives from peers. One way of achieving this might be to make it clear to all children that supporting aggressive behaviour is as unacceptable as aggression itself and by rewarding peers who behave appropriately [see Roderick et al, 1997, for an example of rewarding appropriate playground behaviour]. However, further research would be needed to test the efficacy of such a strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A strong research-based argument has been advanced in the literature for the provision of cooperative, age-appropriate activities for children on the playground. Research findings from a number of studies indicate that providing structured activities matched to the age and gender of the children and close monitoring of children as they engage in these activities resulted in an increase in prosocial behaviour among children and an increase in cooperative play (Bay-Hintz, Peterson, and Quilitch 1994;Leff, Costigan, and Power 2004;Leff et al 2003;Murphy, Hutchison, and Bailey 1983;Roderick, Pitchford, and Miller (1997). Murphy, Hutchinson, and Bailey (1983) found that dividing the playground into sections for different age groups and providing cooperative games for children resulted in a reduction in aggressive behaviour.…”
Section: Playground Supervision Issuesmentioning
confidence: 96%
“…Training playground supervisors would appear to be essential if intervention programmes are to be implemented successfully. Roderick, Pitchford, and Miller (1997) found that training playground supervisors to reinforce children's prosocial behaviour contributed to a reduction in aggressive behaviour. Leff, Costigan, and Power (2004) found that active adult supervision was associated with higher levels of interactions between children from different ethnic backgrounds.…”
Section: Playground Supervision Issuesmentioning
confidence: 98%
“…Roderick, Pitchford, and Miller 1997) for providing a consistent, easy to administer system that provides highly situated short-term impact. Such systems are also critiqued for the same reasons.…”
Section: Rewardsmentioning
confidence: 99%